1975
DOI: 10.1084/jem.142.5.1241
|View full text |Cite
|
Sign up to set email alerts
|

Properties of antigen-specific suppressive T-cell factor in the regulation of antibody response of the mouse. I. In vivo activity and immunochemical characterization.

Abstract: Our previous publications (1, 2) indicated that thymocytes and spleen cells of mice that had been immunized with a high dose of carrier antigen, when transferred into syngeneic host, could suppress the antibody response against a hapten coupled to the homologous carrier . This suppressive effect was found to be mediated by a population of thymus-derived lymphocytes, whose activity was completely abrogated by the treatment with anti-B and complement . Moreover, the specificity of the observed suppression has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(75 citation statements)
references
References 23 publications
4
71
0
Order By: Relevance
“…Studies from our laboratories have also demonstrated major shifts in total Ig synthesis, including profound enhancement, in coculture experiments with PBL from normal donors and patients with hypogammaglobulinemia (31). By contrast, however, other investigators have demonstrated highly restricted suppressor activity, including suppression of specific Ig allotypes (11,12), idiotypes (13,14), class (15), and antibodies (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 97%
“…Studies from our laboratories have also demonstrated major shifts in total Ig synthesis, including profound enhancement, in coculture experiments with PBL from normal donors and patients with hypogammaglobulinemia (31). By contrast, however, other investigators have demonstrated highly restricted suppressor activity, including suppression of specific Ig allotypes (11,12), idiotypes (13,14), class (15), and antibodies (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 97%
“…As the source of antigen-specific suppressor T cells, mice were immunized with two intraperitoneal injections of 100 /~g soluble KLH at a 2-wk interval as described previously (8). Other mice were immunized with 100/~g of DNP-KLH or KLH alone in aluminum hydroxide gel (alum) together with 1 × 109 killed Bordetella pertussis vaccine.…”
Section: Methodsmentioning
confidence: 99%
“…Keyhole limpet hemocyanin (KLH) was obtained from Calbiochem, San Diego, Calif. Dinitrophenylated KLH (DNPT~o-KLH) was prepared by the method described previously (8). Egg albumin recrystallized five times was purchased from Nutritional Biochemicals Corporation, Cleveland, Ohio.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, based on the Ia specificities examined, both the I-A (Ia.1, 3, 15) and I-C (Ia.7) subregions (2) should contain glycosyl transferase genes. Second, the close relationship between Ia antigens and many T-cellderived immunoregulatory substances (10)(11)(12) suggests that carbohydrates may play a role in T-B cell collaboration. Finally, the fact that Ia antigens are oligosaccharide in nature must be borne in mind when attempts are made to develop a relationship between Ia antigens and Ir genes and their role as recognition units.…”
Section: Inhibition Of Anti-ia3 By D-galactose and Related Sugarsmentioning
confidence: 99%